Genealogy of metaphysics of light by Mechtchild von Magdeburg - Viacheslav Stepanov (Cхід, 2013)
The article focuses on the problem of reconstruction of genealogy determining formation of metaphysics of light by Mechtchild von Magdeburg. The author combines retrospective and prospective approaches, which allowed revealing of mystical tradition lasting from Neo-Platonism through the works by pseudo-Dionysius to the medieval mysticism. Metaphysics of light proved to be imaginary supplement to the synthesis of apophatic and cataphatic means sustaining knowledge of God.